Lipopolysaccharide From E. coli Increases Glutamate-Induced Disturbances of Calcium Homeostasis, the Functional State of Mitochondria, and the Death of Cultured Cortical Neurons - Bakaeva, Zanda; Lizunova, Natalia; Tarzhanov, Ivan; Boyarkin, Dmitrii; Petrichuk, Svetlana; Pinelis, Vsevolod; Fisenko, Andrey; Tuzikov, Alexander; Sharipov, Rinat; Surin, Alexander (Frontiers in Molecular Neuroscience, 2022)
Lipopolysaccharide (LPS), a fragment of the bacterial cell wall, specifically interacting with protein complexes on the cell surface, can induce the production of pro-inflammatory and apoptotic signaling molecules, leading to the damage and death of brain cells. Similar effects have been noted in stroke and traumatic brain injury, when the leading factor of death is glutamate (Glu) excitotoxicity too. But being an amphiphilic molecule with a significant hydrophobic moiety and a large hydrophilic region, LPS can also non-specifically bind to the plasma membrane, altering its properties. In the present work, we studied the effect of LPS from E. coli alone and in combination with the hyperstimulation of Glu-receptors on the functional state of mitochondria and Ca2+ homeostasis, oxygen consumption and the cell survival in primary cultures from the rats brain cerebellum and cortex. In both types of cultures, LPS (0.1-10 μg/ml) did not change the intracellular free Ca2+ concentration ([Ca2+]i) in resting neurons but slowed down the median of the decrease in [Ca2+]i on 14% and recovery of the mitochondrial potential (ΔΨm) after Glu removal. LPS did not affect the basal oxygen consumption rate (OCR) of cortical neurons; however, it did decrease the acute OCR during Glu and LPS coapplication. Evaluation of the cell culture survival using vital dyes and the MTT assay showed that LPS (10 μg/ml) and Glu (33 μM) reduced jointly and separately the proportion of live cortical neurons, but there was no synergism or additive action. LPS-effects was dependent on the type of culture, that may be related to both the properties of neurons and the different ratio between neurons and glial cells in cultures. The rapid manifestation of these effects may be the consequence of the direct effect of LPS on the rheological properties of the cell membrane.